Clinical correlates of comorbid attention deficit hyperactivity disorder in adults suffering from bipolar disorder: A meta-analysis. (January 2023) - Bartoli, Francesco; Callovini, Tommaso; Cavaleri, Daniele; Cioni, Riccardo Matteo; Bachi, Bianca; Calabrese, Angela; Moretti, Federico; Canestro, Aurelia; Morreale, Marco; Nasti, Christian; Palpella, Dario; Piacenti, Susanna; et al.
Objective: Attention deficit hyperactivity disorder is a frequent comorbid condition in adults with bipolar disorder. We performed a meta-analysis aimed at assessing sociodemographic and clinical correlates of attention deficit hyperactivity disorder in bipolar disorder. Method: We searched main electronic databases up to June 2021. Random-effects meta-analyses, with relevant meta-regression and quality-based sensitivity analyses, were carried out to estimate the association between attention deficit hyperactivity disorder and putative correlates, grading the quality of evidence. Results: We included 43 studies, based on 38 independent samples. Attention deficit hyperactivity disorder participants were more likely to be males (odds ratio = 1.46; p < 0.001) and unemployed (odds ratio = 1.45; p = 0.045), and less likely to be married (odds ratio = 0.62; p = 0.014). They had an earlier onset of bipolar disorder (standardized mean difference = −0.36; p < 0.001); more mood episodes (standardized mean difference = 0.35; p = 0.007), particularly depressive (standardized mean difference = 0.30; p = 0.011) and mixed (standardized mean difference = 0.30; p = 0.031) ones; higher odds of using antidepressants (odds ratio = 1.80; p = 0.024) and attempted suicides (odds ratio = 1.83; p < 0.001) and lower odds of psychotic features (odds ratio = 0.63; p = 0.010). Moreover, they were more likely to have generalized anxiety disorder (odds ratio = 1.50; p = 0.019), panic disorder (odds ratio = 1.89; p < 0.001), social phobia (odds ratio = 1.61; p = 0.017), eating disorders (odds ratio = 1.91; p = 0.007), antisocial personality disorder (odds ratio = 3.59; p = 0.004) and substance (odds ratio = 2.29; p < 0.001) or alcohol (odds ratio = 2.28; p < 0.001) use disorders. Quality of the evidence was generally low or very low for the majority of correlates, except for bipolar disorder onset and alcohol/substance use disorders (high), and suicide attempts (moderate). Conclusion: Comorbid bipolar disorder/attention deficit hyperactivity disorder may have some distinctive clinical features including an earlier onset of bipolar disorder and higher comorbid alcohol/substance use disorder rates. Further research is needed to identify additional clinical characteristics of this comorbidity.